2001
DOI: 10.2460/ajvr.2001.62.1387
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and toxic effects of lithium chloride after intravenous administration in conscious horses

Abstract: Distribution of lithium best fit a 3-compartment model, and clearance of the electrolyte was slow. Healthy horses remained unaffected by LiCl at doses that exceeded those required for determination of cardiac output. Peak serum concentrations were less than steady-state serum concentrations that reportedly cause toxic effects in other species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
1
36
6
Order By: Relevance
“…Animals were treated with lithium intraperitoneally instead of per os because the latter treatment evokes more pronounced renal problems to experimental species with compared to those after other routes of administration [36]. In addition, the administration of lithium other than per os causes good lithium distribution [37]. Animals in groups of four were sacrificed 1 day, 2, and 12 months after the last injection.…”
Section: Lithium Administrationmentioning
confidence: 99%
“…Animals were treated with lithium intraperitoneally instead of per os because the latter treatment evokes more pronounced renal problems to experimental species with compared to those after other routes of administration [36]. In addition, the administration of lithium other than per os causes good lithium distribution [37]. Animals in groups of four were sacrificed 1 day, 2, and 12 months after the last injection.…”
Section: Lithium Administrationmentioning
confidence: 99%
“…In this regard, expression of genes encoding the adherens junction component E-cadherin and the hemidesmosome component integrin α6 was not suppressed in horses with starch gruel-induced laminitis (Fig S4) and E-cadherin protein expression was not suppressed (Fig S2, panel F) supporting the possibility that adherens junctions and hemidesmosomes might be restored by sustaining β-catenin expression, e.g., through administration of agents that inhibit GSK3β [46]. This attractive possibility is contradicted by studies showing that protein expression of integrin α6 and anchoring filaments BP180 and laminin 5 is reduced in horses with oligofructose-induced laminitis based on immunofluorescence staining [47], consistent with complex disruption of the hemidesmosome.…”
Section: Discussionmentioning
confidence: 82%
“…The results of that study indicated that LiDCO was more reliable than conventional thermodilution cardiac output measurement. The dose of lithium needed (0.15–0.3 mmol for an average adult) is very small and has no known pharmacological effects [10,11]. …”
Section: Technology Questionnairementioning
confidence: 99%